1981
DOI: 10.1002/star.19810331207
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactic Acid in Corn Steeping and Its Relation with Starch Isolation

Abstract: Corn grains were steeped in fresh SO2 solution (300 ppm), old SO2 solution (100 ppm, 0.55 g lactic acid per 100 ml) and fresh SO2 with chemically pure lactic acid (100 ppm SO2 + 0.55 g lactic acid per 100 ml). The water absorption rate in all trials using old SO2 or low SO2 with lactic acid in the first stage of the steeping process was higher. The solubilization and diffusion of protein was stronger in corn grains steeped completely in old SO2 or low fresh SO2 with lactic acid. Such treatments gave the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…The fiber fraction dropped from 3.1 to 13.1%, depending upon the hybrid, with the addition of 0.55% lactic acid. This increase in starch yield with decrease in the fiber fraction is in agreement with other studies (Roushdi et al 1981a, Eckhoff and Tso 1991, Du et al 1996.…”
Section: Effect Of Hybrid and Lactic Acid Level On Starch Yieldsupporting
confidence: 93%
See 1 more Smart Citation
“…The fiber fraction dropped from 3.1 to 13.1%, depending upon the hybrid, with the addition of 0.55% lactic acid. This increase in starch yield with decrease in the fiber fraction is in agreement with other studies (Roushdi et al 1981a, Eckhoff and Tso 1991, Du et al 1996.…”
Section: Effect Of Hybrid and Lactic Acid Level On Starch Yieldsupporting
confidence: 93%
“…Lactic acid is produced to a level of 0.6 to 2.0% during conventional counter-current steeping (Watson et al 1955). Some of lactic acid's beneficial effects observed in corn milling are: increased starch yields (Watson et al 1951, Roushdi et al 1981a, Eckhoff and Tso 1991, increased gluten filtration rate (Watson 1984), decreased evaporator fouling (Watson 1984), increased kernel softening (Cox et al 1944, Roushdi et al 1981a, Earp et al 1985, Shandera et al 1995, increased rate of water uptake (Cox et al 1944, Roushdi et al 1981a, Ruan et al 1992, and increased rate of SO 2 absorption (Shandera et al 1995).…”
mentioning
confidence: 99%
“…Therefore, and Watson et al (1951) recommended addition of lactic acid to the steeping solution in the laboratory. Roushdi et al (1981) and Eckhoff and Tso (1991a) reported decreased starch yields of 4-6% in batch steeping corn when lactic acid was not used.…”
mentioning
confidence: 99%
“…The effect of the concentration of SO 2 in steepwater on the starch recovery was analyzed by Roushdi et al (1981). They found that samples steeped in low concentrations of SO 2 containing lactic acid produced high starch yields with low protein content.…”
mentioning
confidence: 99%